Efficient Ray Tracing Through Aspheric Lenses and Imperfect Bokeh Synthesis - Joo, Hyuntae; Kwon, Soonhyeon; Lee, Sangmin; Eisemann, Elmar; Lee, Sungkil (Computer graphics forum, 2016)
We present an efficient ray‐tracing technique to render bokeh effects produced by parametric aspheric lenses. Contrary to conventional spherical lenses, aspheric lenses do generally not permit a simple closed‐form solution of ray‐surface intersections. We propose a numerical root‐finding approach, which uses tight proxy surfaces to ensure a good initialization and convergence behavior. Additionally, we simulate mechanical imperfections resulting from the lens fabrication via a texture‐based approach. Fractional Fourier transform and spectral dispersion add additional realism to the synthesized bokeh effect. Our approach is well‐suited for execution on graphics processing units (GPUs) and we demonstrate complex defocus‐blur and lens‐flare effects.